Advances in Chimeric Antigen Receptor T-cell therapy for hematologic malignancies and autoimmune conditions: a review of the 2024 American Society of Hematology Annual Meeting - Davis, Samuel; Lutfi, Forat (Frontiers in Hematology, 2025)
Recent advancements in Chimeric Antigen Receptor T cell (CAR T) therapies and manufacturing technologies have expanded treatment options for patients with hematologic malignancies and autoimmune diseases. This review synthesizes the findings from abstracts and oral presentations delivered at the 66th American Society of Hematology (ASH) Annual Meeting. The clinical trial data featured in this review highlights the safety and efficacy of next-generation CAR T constructs, the efficiency of emerging manufacturing technologies, and the expanded indications for CAR T cell therapeutics.